Numerical simulation study of organic nonvolatile memory with polysilicon floating gate - 闫兆文 王娇 乔坚栗 谌文杰 杨盼 肖彤 杨建红 (Chinese physics B, 2016)
A polysilicon-based organic nonvolatile floating-gate memory device with a bottom-gate top-contact configuration is investigated,in which polysilicon is sandwiched between oxide layers as a floating gate.Simulations for the electrical characteristics of the polysilicon floating gate-based memory device are performed.The shifted transfer characteristics and corresponding charge trapping mechanisms during programing and erasing（P/E） operations at various P/E voltages are discussed.The simulated results show that present memory exhibits a large memory window of 57.5 V,and a high read current on/off ratio of ≈ 10~3.Compared with the reported experimental results,these simulated results indicate that the polysilicon floating gate based memory device demonstrates remarkable memory effects,which shows great promise in device designing and practical application.